Power-plant control and instrumentation the control of boilers and HRSG systems - Lindsley, David (London, United Kingdom Institution of Engineering and Technology, 2000)
The book reviews developments in the following fields: steam generation; steam circuits; water circuits; fuel gas circuits; combustion control; draught control; feed water control; steam temperature control; control equipment practice and refurbishing system.
Also available in print version.
Electronic reproduction.
Keywords: Power-plants.; Boilers; Temperature control; Electronic books